Miskonsepsi dalam Pembelajaran IPA: Studi Kasus Madrasah Ibtidaiyah di Tuban Jawa Timur - Lestari, Sri; Rosyidiyah, Nafilah Alimatur; Sari , Uut Kenanga (Tarunateach: Journal of Elementary School, 2025)
The learning of Natural Sciences (IPA) in Madrasah Ibtidaiyah (MI) plays an important role in shaping students' understanding of natural phenomena and scientific concepts. However, misconceptions are still found among students regarding the IPA material being studied. This study aims to identify concepts, theories, laws, and scientific facts in IPA learning and to understand the causes and forms of misconceptions that occur at MI Hidayatun Najah Tuban. The method used is qualitative with data collection techniques in the form of observation and interviews. The results of the study show that the use of cooperative learning methods, practical media, and the environment as learning resources can improve students' understanding, although misconceptions are still found in aspects of collaboration and students' conceptual understanding. These findings indicate the importance of the teacher's role in accompanying students and choosing a contextual approach to reduce misconceptions.